Closer - Nichols, Mike; Marber, Patrick, 1964-; Roberts, Julia, 1967-; Law, Jude, 1972-; Portman, Natalie, 1981- (Culver City, CA : Sony Pictures Home Entertainment, 2005)
Two successful and seemingly loving couples meet and engage in seduction, lies and betrayal.
Based on the play by Patrick Marber.
Originally released as a motion picture in 2004.
Features: music video "The Blower's Daughter" performed by Damien Rice, previews.
Julia Roberts, Jude Law, Natalie Portman.
MPAA rating: R.
DVD, Dolby digital 5.1 surround.
Keywords: Marber, Patrick -- Film and video adaptations; Man-woman relationships -- Drama; Adultery -- Drama; Video recordings for hard of hearing people; Based on the book; Feature films